Efektivitas Promosi Peningkatan Gizi Pada Ibu Hamil Kekurangan Energi Kronik Studi Di Wilayah Kabupaten Mojokerto - Rifaatul Laila Mahmudah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
Pregnant women with nutritional and health problems have an impact on the health, safety of mothers, babies and the quality of babies born. The purpose of this study was to determine The Effectiveness of Promotion of in Creased Nutrition in Pregnant Women with Chronic Energy Deficiency in Kabupaten Mojokerto.The design was Pre Experimental, using One-Group Pretest-Posttest with accidental sampling technique consisted of 10 respondents.The results showed the level of nutrition knowledge of half respondents before being given health promotion was in the less category as many as 5 people (50.0%). On the 3rd day, shown most of the respondent’s in sufficient categories as many as 6 people (60.0%). On the 6th day almost all were in the good category as many as 8 people (80.0%). Used Wilcoxon Signed Rank Test statistical test with a value of 0.011, there is influence of Effectiveness of Promotion of in Creased Nutrition in Pregnant Women with chronic energy deficiency. Creased Nutrition isnot only behavior change but also changing their environment.So it is necessary to do Effectiveness of Promotion every month to influence the behavior of pregnant women with chronic energy deficiency and prevent the problem of chronic energy deficiency